Explaining the unmet information needs of family carers of people with dementia: a theoretical model of information behaviour - Chiara De Poli (BMC Geriatrics)
Abstract Background Family carers of people with dementia often report unmet information needs, despite policy emphasis on the provision of information as key to enabling good care and empowering carers in their role. Although the consequences of unmet information needs are detrimental to both the person being cared for and the carer, a systematic understanding of the causes of unmet information needs is lacking. To address this gap, this article presents a theoretical framework centred on the concept of information behaviour and integrating the information seeking and communication model, candidacy theory, and discrepancy theory. The framework maps information behaviour across six phases (from the identification of an information need to its satisfaction) and three levels (individual, service, system) at which explanatory factors may be observed. Methods The framework was tested on data collected from 24 in-depth interviews and two focus groups with people with dementia and family carers of someone living with dementia in the North-East of England (UK). Data were analysed thematically to map the factors at play at each phase of the framework that might explain whether needs were met. Results Unmet information needs are not always the result of a lack of information. Issues such as inadequate support for the user in identifying the need, problems in finding information, the timing of information provision, the amount of information provided, the credibility of the information source, and the relevance of the information (given care needs, preferences, personal, and family circumstances) can all contribute to unmet information needs. This work shows that meeting an information need ultimately requires progress through the different stages of information behaviour, each of which is influenced by the interplay of individual-, service-, and system-level factors, and depends on both users and providers. Conclusions This work challenges the rational paradigm in health and care information, which assumes that more information will lead to better care, and contributes to a critical perspective on health and care information that reframes successful information behaviour as a set of complex activities that are relational, emotionally charged, contextually embedded, and require (and produce) situated knowledge. Trial registration Not applicable.